Quand la trace écrite dessine le parcours de l’autonomie : l’expérience de la revue Lapis - Francesca Sensini (Laboratoire Italien)
The quarterly journal Lapis. Percorsi della riflessione femminile began life in Milan on 1 January 1987, and remained active until 1996, publishing a total of 32 issues. The editor-in-chief was Lea Melandri, a philosopher, essayist, and activist in the feminist movement in Italy. The publishing project was not driven by a clearly defined and permanent group of female writers. On the contrary, Lapis sought to create an open space for reflections, testimonies, and stories from the world of women, starting with individual experiences, beyond any temptation to symbolism and metaphysics. Our paper aims to highlight how Lapis engaged in the most innovative and potentially revolutionary feminist practices of the 1970s, particularly the analysis of suppressed themes—such as the connection between love and violence, the dynamics of emotional and sexual life, and the problems created by the dualist vision specific to the patriarchy—which silently influence the network of human relations in both private and public life.